Multimodality treatment for poorly differentiated neuroendocrine head and neck carcinomas – a single institution experience. (23rd May 2013) - Görner, M.; Brasch, F.; Hirnle, P.; Gehl, H.‐B.; Scholtz, L.‐U.; Wegehenkel, K.; Sudhoff, H.
<x xml:space="preserve">Abstract</x> Poorly differentiated head and neck neuroendocrine neoplasms are very rare. Surgical resection alone is insufficient to control the disease because of the high incidence of metastases. However, due to the lack of randomised clinical trials, treatment recommendations for this cancer vary considerably and are based on a limited number of small retrospective studies. We performed a retrospective analysis of all patients treated at our institution between 2003 and 2011. We assessed the stage of disease, type of therapy, toxicity, treatment response, time to progression and overall survival for all cases. Ten patients received combined modality treatment with chemotherapy in addition to surgery or radiation or both. According to Response Evaluation Criteria In Solid Tumours (RECIST) criteria, six of nine evaluable patients achieved complete remission and three patients had a partial remission. The mean duration of response was 358 days, with a range from 141 to 1080 days. The overall 1‐year survival rate was 88%; however, only approximately 50% of patients were alive after 2 years. Multimodality treatment concepts induce high initial remission rates in poorly differentiated neuroendocrine head and neck carcinomas. However, the time to relapse is usually short, and therefore long‐term prognosis of this rare head and neck tumour remains poor.